Ambipolar Transporting 1, 2‐Benzanthracene Derivative with Efficient Green Excimer Emission for Single‐Layer Organic Light‐Emitting Diodes. Issue 2 (12th February 2013) - Duan, Lian; Qiao, Juan; Sun, Yongduo; Zhang, Deqiang; Dong, Guifang; Wang, Liduo; Qiu, Yong
<x xml:space="preserve">Abstract</x> Single‐layer organic light‐emitting diodes (OLEDs) are highly desired due to their potential advantages such as simplifying the fabrication process and lowering the cost. However, high‐performance single‐layer OLEDs are rare in the literature as they require bipolar transporting materials with balanced electron and hole mobilities, high fluorescent quantum yields, and good energy levels matching both electrodes. In this work, a bipolar transporting benzanthracene derivative, namely 7, 12‐bis‐[4‐(2, 2‐diphenylvinyl)‐phenyl] benzanthracene (BDPBan), is designed and synthesized without any structural motifs for hole and electron transport. As electrons and holes can perform intermolecular hopping to similar spatial extents between the adjacent benzanthracene moieties, well‐balanced hole and electron mobilities higher than 10−3 cm2/Vs are achieved. Though the strong intermolecular interactions facilitate the formation of excimers in concentrated solutions and thin films of BDPBan, efficient undoped single‐layer OLEDs are fabricated with strong green emission from the excimers. A device with 90 nm BDPBan as the emitting layer shows a peak current efficiency of 11.4 cd/A: beyond the conventional upper limit calculated based on the photoluminescence quantum yield.